Tests Of Fiber-Reinforced Shotcrete At The Chief Joseph Mine, Butte, Montana - Lewis A. Martin (The National Institute for Occupational Safety and Health (NIOSH), 2004)
Researchers from the Spokane Research Laboratory, National Institute for Occupational Safety and Health, in cooperation with engineers from the Department of Mining and Geological Engineering, Montana Tech, Butte, MT, conducted tests to evaluate the tensile strength, fiber count, and adhesion of shotcrete applied to panels at the Chief Joseph Mine, a research and training facility operated by Montana Tech. The tests were conducted in the mine ramp 45 m (150 ft) inward from the access portal at a 15.25-m- (50-ft) long test area divided into five 3-m- (10-ft) long sections. The shotcrete was applied with an Aliva 240.5 machine fitted with a predampener. Different amounts of fiber were entrained for each panel. Background data for the tests were obtained from earlier tests in Nevada, where the typical amount of fiber in the shotcrete is 6.54 kg/m3 (11 lb/yd3). All shotcrete was applied to a minimum thickness of 76 mm (3 in). Cylindrical cores were drilled at the wall-rock interface, and adhesion was tested after 28 days of curing. The goal of this research is to reduce the need to install multiple supports at the advancing face by creating a safer mining system that limits the time miners are exposed to unprotected roof.